PENGARUH PERBAIKAN METODE PEMBAGIAN BATANG TERHADAP WAKTU KERJA DAN PRODUKTIVITAS PENEBANGAN HUTAN ALAM PRODUKSI: STUDI KASUS DI PT. DWIMAJAYA UTAMA - Soenarno; Yuniawati (Jurnal Penelitian Hasil Hutan, 2019)
The improvement of bucking method in tree felling was examined to observe harvesting efficiency in natural production forest. This paper studies distribution of work time elements, productivity, and efficiency of timber utilization in accord with application of bucking system improvement. Research was conducted in natural forest production concession of PT. Dwima Jaya Utama in Central Kalimantan. The study was conducted using four research sample plots (PCP) measuring of 100 m x 200 m which were placed intentionally (purposive) on selected cutting plots. Two PCPs were used for the conventional logging treatment (CV) and the remaining plots were allocated for the improving stem distribution methods (IBM). Data analysis was performed statistically using PWSTAT version 23.0. Results showed that the CV method’s working time of 14.6 minutes/tree was not significantly different with that of IBM working time of 15.5 min/tree. Wood utilization efficiency of IBM was 93.1%, which was higher than that of the conventional method (CV) of 85.4 %. However, the productivity of IBM was 27.161 m3/hour, which was lower than that of the CV method of 32.847 m3/hour.